immuneACCESS
DOI: 10.21417/b7305d
|View full text |Cite
|
Sign up to set email alerts
|

T-cell localization, activation and clonal expansion in human pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDA) is a lethal malignancy resistant to most therapies, including immune checkpoint blockade. To elucidate mechanisms of immunotherapy resistance, we assessed immune parameters in resected human PDA. We demonstrate significant interpatient variability in T-cell number, localization, and phenotype. CD8 + T cells, Foxp3 + regulatory T cells and PD-1 + and PD-L1 + cells were preferentially enriched in tertiary lymphoid structures that were found in most tumors compared to stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
89
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(101 citation statements)
references
References 38 publications
12
89
0
Order By: Relevance
“…Also, it may indicate that FoxP3 expression in tumors can be induced by activation per se , without being linked to an immunosuppressive function . This hypothesis is in concordance with a previous study by Stromnes et al ., demonstrating that FoxP3 levels on Tregs from pancreatic tumor tissue were significantly higher than on Tregs in adjacent benign tissue, possibly indicating that FoxP3 is elevated due to activation. This observation may be important for understanding the mechanisms underlying immune evasion in periampullary adenocarcinomas.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, it may indicate that FoxP3 expression in tumors can be induced by activation per se , without being linked to an immunosuppressive function . This hypothesis is in concordance with a previous study by Stromnes et al ., demonstrating that FoxP3 levels on Tregs from pancreatic tumor tissue were significantly higher than on Tregs in adjacent benign tissue, possibly indicating that FoxP3 is elevated due to activation. This observation may be important for understanding the mechanisms underlying immune evasion in periampullary adenocarcinomas.…”
Section: Discussionmentioning
confidence: 96%
“…Most previous studies rely on single markers rather than combinations thereof, disregarding the reciprocal interaction of immune cells. Moreover, the spatial localization of the immune cells appears to bear relevance, and the coappearance of cytotoxic immune cells and cancer cells has recently been recognized as a predictor of response to immunotherapy …”
Section: Introductionmentioning
confidence: 99%
“…the basis of T cell 3D locomotion throughout normal and solid tumor stroma, remain elusive, largely due to the overall complexity of 3D environments and undeciphered phenotype plasticity, such as coexisting amoeboid and mesenchymal modes of motility. Despite the widely acknowledged fact that the steric and structural density, architecture, and mechanics of solid tumors can prevent effective T cell infiltration or distribution (Elahi-Gedwillo et al, 2019;Hartmann et al, 2014;Kuczek et al, 2019;Salmon et al, 2012;Stromnes et al, 2017), the study of mechano-and structure-sensitive aspects of T cell motility has predominantly focused on flat 2D environments (i.e. more mesenchymal-like phenotypes) or confinement in microchannels (Jacobelli et al, 2010;Krummel et al, 2014;Saitakis et al, 2017;Tooley et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…architecture and mechanics) also strongly influence T cell infiltration, and their ability to effectively distribute throughout, and sample, the entire tumor mass. Indeed, the complex stromal reaction in solid tumors can limit access and effective distribution of T cells creating antitumor immunityfree sanctuaries (Elahi-Gedwillo et al, 2019;Hartmann et al, 2014;Kuczek et al, 2019;Salmon et al, 2012;Stromnes et al, 2017). Furthermore, many solid tumors are rich with aligned extracellular matrix (ECM) networks (Best et al, 2019;Provenzano et al, 2006;Ray et al, 2017a) , which provide contact guidance for carcinoma cells (Provenzano et al, 2006(Provenzano et al, , 2008Tabdanov et al, 2018aTabdanov et al, , 2018b, and can also direct migration of infiltrated T cells in solid tumors (Hartmann et al, 2014;Salmon et al, 2012;Wolf et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have evaluated the function of tumour-associated neutrophils (TANs) in PDAC progression, which has been reviewed extensively [37]. In a recent clinical study, neutrophils were found to have an unexpected positive correlation with CD8 + T cells [38]; the correlation was surprising since these cells might play a role in excluding infiltrating T cells from PDAC tissue in mouse models [39,40]. These controversial results may be interpreted as a function of the different neutrophil frequencies in humans and mice.…”
Section: Antitumour Effector Cells and Immunodeficiencymentioning
confidence: 99%